Pemanfaatan Dana Bos untuk Meningkatkan Aktivitas Kesiswaan di Sd Inpres 2 Kamonji - Ahmad Arifudin; Yusdin Bin Mahmudin Gagaramusu; Kadek Hariana (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
The utilization of BOS funds is very important to improve student activities in primary schools, this is because BOS funds have a strategic role in improving the quality of education, particularly in supporting student activities in primary schools. Student activities include various programs that aim to improve students' overall abilities, including academics, arts, sports and character. This study aims to determine the utilization of BOS funds to improve student activities at SD Inpres 2 Kamonji. The method used was descriptive qualitative, with data collection through interviews, observations, and documentation studies. The results showed that the planned and transparent allocation of BOS funds significantly increased student participation in extracurricular activities, training, and competitions, as well as the procurement of supporting facilities and infrastructure. However, problems such as bureaucracy, managers who do not understand, and limited budgets are still problems that must be overcome. BOS funds have great potential to foster a more inclusive learning environment and support the full development of students' potential with better management.